How do programme directors perceive trainee attrition? A qualitative focus group study in three Dutch teaching hospitals - Jacqueline Bustraan; Kirsten Dijkhuizen; Erik Driessen; Jan M M van Lith; Arnout Jan de Beaufort; Maartje E D van den Bogaard (BMJ Open)
Objective To gain insight into programme directors’ (PDs’) perceptions of trainee attrition from postgraduate medical education (PGME), focusing on interactions between stakeholders within the learning environment and roles of PDs in the process leading to attrition.Design, setting and participants We performed a focus group study with 27 PDs from three Dutch teaching hospitals and analysed transcripts using template analysis.Results PDs identified attrition as a multilevel problem, in which personal, workplace and system-bound factors play a role. PDs mentioned balancing professional and personal responsibilities, in particular parenthood and high ambitions, as important trainee-related factors. PDs adopt different, at times conflicting, roles when guiding trainees, for example, assessor and mentor, and they struggle to balance these roles. They displayed various emotions when discussing attrition, varying from disappointment to frustration and anger, yet could also frame attrition positively as new opportunity. PDs used numerous resources to support trainees in difficulty, in a reactive rather than in a pro-active manner. A generation difference between faculty and trainees regarding work-life balance was mentioned as impeding mutual understanding. On the system level, PDs observed how implicit beliefs and negative interactions between actors in the learning environment impede trainees’ well-being.Conclusions PDs perceived trainee attrition as a multi-level problem that highlighted conflicting roles for the PD and evoked a wide range of emotions. The authors propose the following interventions: (1) address conflicting roles of PDs by reallocating specific tasks to other independent ‘third parties’, for example, professional coaching; (2) implement pro-active support for trainees unrelated to assessment; (3) create awareness of implicit assumptions of stakeholders and promote social belonging; (4) foster a supportive learning climate with clinical leaders as role models.